THE LAW OF ONLINE ZAKAT BASED ON THE APPLICATION PROVIDING EASINESS IN TRANSACTION OF ZAKAT PAYMENT - Sari Utami (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2020)
The importance of zakat distribution in the digital age increasingly shows the existence and urgency of digitalization in all aspects. The purpose of zakat distribution online will facilitate muzakki effectively and efficiently in terms of activities and time in distributing zakat evenly and thoroughly to break the poverty chain, and improve social and economic welfare of the community without having to distinguish between the rich and poor, because behind the distribution of zakat funds is the rights of those who are entitled to receive it (mustahik). This research focused on qualitative research using a descriptive analysis technique which is to conduct an analysis by describing, describing, explaining about paying zakat online in Islamic law. In Islamic view, zakat which is done online is permissible because one of the reasons is that it is only different in form of distribution, namely the transition from manual to automatic. From those who usually come to the institution to pay directly but this time only by accessing and transferring. However, it still does not abandon the terms or conditions in issuing or distributing zakat. Distribution of zakat online is not a problem in terms of Islamic law, because its distribution will facilitate muzakki or Muslims who have an obligation to pay zakat. A muzakki can distribute his zakat online is legal and not a problem legally. Special institutions that are given the mandate in the distribution of zakat will be managed because it is deposited from muzakki which is distributed online and must be in accordance with the principles in sharia provisions. So that the obligation to fulfill or pay zakat continues to be carried out in order to share with others who are entitled to need throughout Indonesia.Keywords: Easiness; Islamic Law; Online; Zakat.